(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article explores the methodological foundations of developing basic physical qualities in youth. The importance of improving strength, endurance, agility, speed, and flexibility is emphasized as key elements in fostering overall physical preparedness, healthy lifestyle habits, and psychological resilience. Various principles, pedagogical approaches, and practical tools for enhancing youth’s physical fitness are discussed.